2020
DOI: 10.22495/cocv18i1siart12
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ remuneration, corporate governance and firm performance linkages: Evidence from the emerging country

Abstract: The study examines the trends and patterns in remuneration of directors working for the largest 30 listed companies in India over the past 18 years, i.e., from 2002 to 2019. It tries to establish short-term and long-run relationships between the director’s remuneration and firm performance after controlling for the firm’s size, governance, leverage, and risk for the sample companies. The study found a significant increase in remuneration for the period of study, especially after the new guidelines on executive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the other hand, smaller boards are preferred by companies for avoiding free-riding benefits and quick decision-making (Kumar & Singh 2013) thus, better impact on firm value (Eisenberg et al 1998). Also, smaller boards keep control of the excessive remuneration of directors (Soni & Singh 2020). Also, studies like Martin and Herroro (2018) reported no significant relationship between board size and firm performance.…”
Section: Literature Review Theory and Hypotheses Developmentmentioning
confidence: 98%
“…On the other hand, smaller boards are preferred by companies for avoiding free-riding benefits and quick decision-making (Kumar & Singh 2013) thus, better impact on firm value (Eisenberg et al 1998). Also, smaller boards keep control of the excessive remuneration of directors (Soni & Singh 2020). Also, studies like Martin and Herroro (2018) reported no significant relationship between board size and firm performance.…”
Section: Literature Review Theory and Hypotheses Developmentmentioning
confidence: 98%
“…Meanwhile, the theoretical perspective and research outcomes have remained contentious and inconclusive. Some scholars view CEO pay as a reward for performance by stressing performance‐based pay for CEOs (Adeusi, 2021; Bhuyan et al, 2022; Buck et al, 2008; Edem et al, 2021; Fama, 1980; Jatana, 2023; Kurawa & Kabiru, 2014; Obembe et al, 2016; Olaniyi & Obembe, 2017; Olaniyi, Obembe, & Oni, 2017; Olaniyi & Olayeni, 2020; Saidu & Alkhawlani, 2017; Soni & Singh, 2020; Umobong & Bele–Egberi, 2019). The principle underlies performance as a major determinant of CEO pay (Khursheed & Sheikh, 2022; Kweh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%